International journal of secure software engineering (IGI Global (701 E. Chocolate Avenue, Hershey, Pa., 17033, USA), 2010)
The International Journal of Secure Software Engineering (IJSSE) publishes original research discussing methods and applications of systematic, quantifiable approaches to the development, operation, and maintenance of secure software systems. IJSSE addresses the problem of development duality between constructing a functional software system and constructing a secure system at the same time. Emphasizing security issues of software from a software engineering perspective, this journal promotes the idea that security issues must be an integral part in every phase of software development and advocates the development of security-aware software systems from the ground up.